FAKTOR- FAKTOR YANG MEMPENGARUHI TERPAPARNYA COVID 19 PADA PENDERITA BERGEJALA DAN TANPA GEJALA DI KOTA TANGERANG - Bangun Wijonarko; Nasihin Nasihin; Dina Sri Mawaddah (Jurnal Medikes (Media Informasi Kesehatan), 2021)
The COVID-19 outbreak has been declared a Global Public Health Emergency by the World Health Organization (WHO) on January 30, 2020. Various obstacles are faced by the government in preventing the spread of covid 19 because there are factors that affect the public's lack of awareness in complying with protocols in preventing COVID -19. Objective: To determine the factors that influence the exposure of covid 19 in symptomatic and asymptomatic patients in Tangerang City. Methods: This research is an analytic study with a Cross-Sectional approach. the population is all confirmed people according to secondary data from the Tangerang City Health Office with a total of 608 people taken from March 2 to August 5, 2020. A total sample of 241 respondents was taken by random sampling. Analysis technique with chi-square test. Results: from the relationship test, these factors included age with p = 0.763 no relationship, sex p = 0.895 no relationship, confirmed contact history p = 0.007 no relationship, travel history p = 0.036 no relationship, history of co-morbidities p = 0.022 there is a relationship. Conclusion: age, gender showed no relationship with exposure of COVID-19. Meanwhile, the contact history, travel history, and history of co-morbidities showed a relationship with exposure of COVID-19.